Lack of Association of 1513 A/C Polymorphism in P2X7 Gene with Susceptibility to 7 Pulmonary and Extrapulmonary Tuberculosis - Ozdemir, Fethi Ahmet; Erol, Deniz; Konar, Vahit; Yuce, Hueyin; Senli, Ebru Kara; Bulut, Funda; Deveci, Figen (Turkish Assoc Tuberculosis & Thorax, 2014)
Introduction: Tuberculosis, is one of the a leading causes of death worldwide, is characterized by different clinical forms including: latent, localized pulmonary infection and extrapulmonary tuberculosis. Candidate gene association studies have implicated common polymophisms in genes that may influence the development of tuberculosis. This study, aimed to elucidate the role of P2X(7) gene in 1513A/C polymorphism the etiopathogenesis of tuberculosis. Materials and Methods: The study included 160 patients with tuberculosis (71 pulmonary and 89 extrapulmonary tuberculosis) and 160 healthy controls. Genomic DNA was isolated and 1513A/C polymorphism in P2X(7) gene was genotyped by PCR-RFLP method. Results: Frequency of P2X(7) AA genotype was 47.5% in controls and 56.87% in patients, AC frequency was 39.37% controls and 32.5% in patients, CC genotype was 13.12% in controls and 10.62% in patients. No significant difference in allele and genotype frequencies (1513A/C polymorphism) between tuberculosis patients and controls was found. Conclusion: The results suggest that 1513A/C polymorphism of P2X(7) gene is not associated with pulmonary and extrapulmonary tuberculosis in the Eastern Turkey.
Pulmoner ve ekstrapulmoner tüberkülozlu hastalarda P2X7 genindeki 1513 A/C polimorfizmin hastali{dotless}kla i?lişkisinin olmamasi{dotless}
Keywords: Tuberculosis; P2X(7); polymorphism